Impact of Exercise on the Course of Parkinson’s Disease: A Systematic Review - Sadowska, Aleksandra; Welkier, Aleksandra; Sobiński, Adam; Miśkiewicz, Joanna; Dudek, Aleksandra; Pietrusińska, Patrycja; Moder, Jakub; Dziewierz , Anna; Kwaśniewska, Paula; Śliwa-Tytko, Patrycja (Quality in Sport, 2025)
Aim of the study The aim of this article is to review scientific research on the impact of physical activity on the progression of Parkinson’s disease. Specifically, we will discuss the quality of life of patients with Parkinson’s disease, various types of physical activity that influence both motor and non-motor symptoms, and the molecular mechanisms through which physical activity affects the human body. Materials and Methods The authors conducted an extensive review of articles available in PubMed, Google Scholar, UpToDate. The keywords Parkinson’s disease, physical activity, quality of life and exercises were the basis of the review. Studies published between 1992 and 2024 were included in the review. Conclusions Physical activity is beneficial for clinical outcomes and quality of life in patients with Parkinson’s disease.